Avaliação da atividade antifúngica in vitro da molécula CH3ISACN sobre espécies de candida albicans e candida glabrata isoladas do trato urinário - Farias, Brenda Kercya da Silva (2023)
Urinary tract infection (UTI) corresponds to the colonization of microorganisms and invasion of any structure of the genitourinary tract. The genus Candida is one of the most prevalent in these infections, with emphasis on the species Candida albicans. However, the number of cases caused by other species such as C. glabrata has grown and represents a worrying factor, as it presents resistance to antifungal agents commonly used in clinical practice. The search for new pharmacological alternatives becomes an important resource to fight these infections. In this perspective, the antifungal potential of the synthetic product derived from isatin 2-(3-hydroxy1-methyl-2-oxoindolin-yl) acrylonitrile (CH3ISACN) was investigated through in vitro studies against strains of C. albicans and C. glabrata . The biological activity of the molecule was evaluated by determining the Minimum Inhibitory Concentration (MIC), Minimum Fungicide Concentration (MFC), association assay using the Checkerboard technique, study of possible mechanisms of action (assays with 0.8M sorbitol and ergosterol 400 µg/mL) and inhibition of biofilm formation. The test product showed remarkable antifungal activity on the strains tested, with a MIC value of 64 µg/mL, which inhibited the growth of 11 (92%) of the 12 strains tested at the concentration, with 7 (87%) of the 8 strains of C. albicans and 100% inhibition for the 4 strains of C. glabrata. The CFM was set at 128 µg/mL, showing a fungicidal effect for most strains tested. The association of CH3ISACN with fluconazole, as well as CH3ISACN with amphotericin B resulted in synergism for C. albicans and indifference for C. glabrata for both standard drugs tested. Through the sorbitol and ergosterol assays, it was observed that the antifungal activity of the investigated molecule probably occurs due to its action on the fungal cell wall. Finally, the molecule showed moderate inhibition of biofilm formation for C. albicans ATCC-76485 and no effect against C. glabrata. In view of the above results, the synthetic molecule can be considered as a possible treatment for fungal infections of the urinary tract caused by Candida species.